Policy Implementation of Community-Led Total Sanitation - Harom, Saepul; Arifianti, Ria; Alexandri, Mohammad Benny (European Journal of Applied Sciences, 2021)
The purpose of this study was to analyze the implementation of the Community-Led Total Sanitation (CLTS) Program in Bandung Regency which has been implemented. This research uses qualitative research methods by analyzing documents, according to the specified research topic, including examining journal article sources, book sources, program policy sources from documents, and conducting interviews with informants focused on finding information guided by relevant documents for research. Findings from the Community-Led Total Sanitation (CLTS) program research show that this Open Defecation Stop begins with facilitator training to community health center sanitarians by the Health Office. The follow-up after the training is carrying out triggering activities, namely stopping open defecation. Implemented with a focus on changing the behavior of each individual in the community not to defecate in the open, followed by utilizing sanitary facilities, namely healthy latrines. Triggering is carried out so that people change attitudes and behavior, from defecating in the open to stop open defecation. The results of the triggering must be monitored to ensure that the community starts taking follow-up actions after the triggering.